The Relationship between Self Efficacies to Academic Cheating in Madrasah Aliyah Islamiyah Sunggal - Mustika, Mustika; Hasmayni, Babby; Sani, Zulqarnain Nur (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to find out The Relationship between Self Efficacies to Academic Cheating in Madrasah Aliyah Islamiyah Sunggal. Based on the results of the calculation of Product Moment Correlation, it is known that there is a negative relationship between self-efficacy and academic cheating, where Rxy = -0.624 with a significant p = 0.000 <0.05. This means that the lower the self-efficacy, the higher the academic cheating. Conversely, the higher the self-efficacy, the higher the academic cheating. The effective contribution of the self efficacy variable to academic cheating in Madrasah Aliyah Islamiyah Sunggal is 38.9%. While the remaining 61.1% is due to other factors such as moral and religious developments. In general, the results of the research on students of Madrasah Aliyah Islamiyah Sunggal had moderate self-efficacy, because the empirical average value was 89,372 which was smaller than the hypothetical average score of 93.00, while academic fraud was moderate, because the empirical average value was 204,117 which was higher greater than its hypothetical mean of 188.